Hot salt corrosion behavior of Ti2AlNb alloys at different temperatures - SUN Guangyao; LIU Shishuang; ZHOU Yi; CAO Jingxia; HUANG Xu (Cailiao gongcheng, 2024)
To enhance the reliability of Ti2AlNb alloys as an aerospace engine component in marine environments， the hot salt corrosion behavior of Ti2AlNb alloy with nominal compositions of Ti-22Al-23Nb-1Mo-1Zr（atom fraction/%） coated with Na2SO4/NaCl（95/5，mass ratio）at temperatures of 550， 650 ℃ and 750 ℃ was investigated.The corrosion mass gain curves of alloys at different temperatures were drawn. The surface morphologies， cross-section structures， and corrosion products of the alloy after hot salt corrosion were examined and analyzed by X-ray diffraction（XRD）， scanning electron microscopy（SEM）， and energy dispersive X-ray spectroscopy（EDS）. The results show that the corrosion rate at 550 ℃ is lower and the oxide scales are straight， dense and intact， exhibiting excellent resistance to hot salt corrosion. The corrosion mass gain curves of the alloy follow a parabolic law at 650℃ and the oxide scales exhibit small-scale peeling and internal cracks， with a slightly layered structure. The alloy exhibits good resistance to hot salt corrosion at 650 ℃ in general. A significant mass loss is observed during the corrosion process at 750 ℃， with the oxide scales cracking and peeling severely. Furthermore， within the oxide scales emerges a distinct layered structure where two layers of corrosion products alternately exist： the main layer is mainly composed of TiO2 and contains various corrosion products including NbAlO4， while the other layer is mainly composed of NaNbO3. The resistance to hot salt corrosion of the alloy decreases seriously at 750 ℃.